ส่วนประสมการตลาดบริการที่มีผลต่อผู้บริโภคในการเลือกร้านอาหารญี่ปุ่นในศูนย์การค้าจังหวัดเชียงใหม่ - รัษดาวรรณ สุดใจ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study aimed to study service marketing mix affecting consumers towards selecting Japanese restaurants at shopping malls in Chiang Mai province. The research data was collected by 400 samples with questionnaires from people who have eaten and serviced Japanese restaurants in amount 4 Shopping malls in Chiang Mai province within 6 months. The data was collected by using convenience sampling and 400 samples were divided in proportion to numbers of Japanese restaurants at shopping malls in Chiang Mai province. The data was analyzed by using descriptive statistics namely frequency, percentage and mean. In addition, the inferential statistics by t-test and One-way ANOVA were also applied in order to find differences between sample groups are gender, frequency of using Japanese restaurants and expenses per time. The results of research revealed that most of respondents’ questionnaires were female in the age of 16-25 years old. There were graduated in Bachelor’s degree, being a student, had average monthly business income lower than 10,000 Baht, consumer spending rationally buy only products that provide good value for money, cause of eating Japanese food in shopping malls is Japanese food are delicious. A Japanese restaurant often to select is Fuji restaurant. Japanese menu often to select is ramen with hot soup. The frequency of using Japanese restaurant is 1-2 times a month. The day of using Japanese restaurant is inaccurate. The timing of using Japanese restaurant is 13.00pm. - 16.00pm. The length of timing for using Japanese restaurant is lower than an hour. The reason of using Japanese restaurants at shopping malls is, they want to eat Japanese food. Colleagues and friends participate in selecting a Japanese restaurant at shopping mall. Expenses for having Japanese food amount 500-1,000 Baht. A number of persons are 2-3 persons per time that they went to Japanese restaurants together. Television is a media that make them knew Japanese restaurants at shopping mall. The favorite promotion they like is discount coupons. They feel impress in using Japanese restaurants at shopping mall in Chiang Mai province every time. The questionnaire respondents to the research regarding “Service Marketing Mix Affecting Consumers Towards Selecting Japanese Restaurants at Shopping Malls in Chiang Mai Province” revealed at the high level all factors of Service Marketing Mix. The first important factor is Product; in sub-factor of taste of Japanese food, the second factor is People; in sub-factor of the concentration of staff and number of staff which enough for service. The third factor is Physical Evidence; in sub-factor of installing air-conditional in restaurant. The fourth factor is Process; in sub-factor of process of concentration service during customer using service. The fifth factor is Price; in sub-factor of reasonable price with quality. The sixth factor is Promotion; in sub-factor of serving complimentary green tea and the seventh factor is Place; in sub-factor of comfortable parking. The result of comparison differences between mean sample groups of Service Marketing Mix Affecting Consumers Towards Selecting Japanese Restaurants at Shopping Malls in Chiang Mai Province revealed that there are differences some sub-factors of Service Marketing Mix in gender, frequency of using Japanese restaurants and expenses per time.